The Role of International Human Rights Law in Fights Against Climate Change - Andika Putra (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2021)
This paper aims to examine the current international legal framework that addresses climate change and identify the role of international human rights law in climate change issues. This paper began by identifying the international legal basis, the development of international legal regimes, and looking at the character and nature of these frameworks. Furthermore, this study seeks to identify the role of international human rights law to close the gap left by the climate change framework. This normative legal research examined secondary data from relevant books, journals, and published documents. There were several findings from this research. First, the current international climate change framework is insufficient to address climate change problems and their adverse impact. Second, international human rights law may play a significant role in closing the current climate change framework gap. International human rights law will add distinctive value to the current system, perform the complementary function to the non-legally binding commitment, and provide an 'arena' for such non-compliance behavior of states parties.